Agent-Based Social Simulations - Srbljinović, Armano (Array, 2014)
We start with a brief introduction to complex systems. Then we briefly review the so-called cellular automata, of which the Game of Life is just one fascinating example. After that we shift attention towards a special kind of computational models called agent-based models, that can be seen as natural extensions of cellular automata. We concentrate on social science applications of these models, review their main properties, ways of their development and of analysing their results.